Pathophysiological Features of Endogenous Intoxication in Pregnant Women with Arterial Hypertension - N. V. Kabanova (Общая реаниматология)
Objective: to determine the nature and specific features of development of endogenous intoxication in pregnant women with arterial hypertension. Subjects and materials. Humoral extracellular fluid volume regulation, partial renal functions, placental hormonal function, membranous lipid peroxidation activity, antiradical defense, the parameters of central hemodynamics, endogenous intoxication, and a biochemical coagulogram were studied and differential blood count with the leukocytic ratio indices was estimated in 172 pregnant females with arterial hypertension and 54 healthy pregnant ones in the third trimester. The statistical package «Stadia» was applied. Results. Arterial hypertension caused by pregnancy was ascertained to involve pathogenetically different types: low-, normal-, and high-renin ones. In pregnant women with arterial hypertension, the general pathogenetic homeostatic changes were placental hormonal imbalance, activated membranous lipid peroxidation, impaired lymph outflow, sodium and water retention, hepatic and renal failure, and endogenous intoxication. Conclusion. Placental ischemia appearing as placental hormonal imbalance (extrarenal pressor system) was accompanied by a compensatory humoral response: arterial hypertension and metabolic disturbances. Changes in medium-weight molecule 280, leukocytic intoxication index, erythrocytic sorption capacity, and Paramecium test, by confirming the presence of endogenous intoxication in pregnant females with arterial hypertension, were caused by a type of arterial hypertension (by the hemodynamic profile and the type of impaired partial renal functions). Key words: pregnancy, arterial hypertension, endogenous intoxication.